Analisis Minat Masyarakat dan Pendapatan Masyarakat terhadap Pegadaian Syariah - Sinaga, Anisa Fitria; Lubis, Atika Atayarisah; Sinaga, Dewi Larasati; Tinambunan, Fitry Ulinda; Amelia, Regita; Saragi, Sarah Lylia; Sitio, Veranita (Ikatan Da'i Indonesia, 2024)
People with low incomes may see sharia pawnshops as a way to obtain additional funds by using their assets as collateral. In this case, their interest in using sharia pawnshops is related to increasing their income. Considering the importance of understanding people's interest and income towards sharia pawnshops, a comprehensive and in-depth analysis is needed. This research aims to analyze what factors influence people's interest in sharia pawnshops, as well as the relationship between people's income and interest in sharia pawnshops. The method used in this research is a literature review, namely a systematic, clear and repeatable identification method. The data source for this research uses secondary data in the form of literature studies by analyzing various reading materials related to people's income, people's interests, and sharia pawnshops.